EFFECT OF MECHANICAL PROPERTIES AND WEAR BEHAVIOUR ON LOCUST BEAN WASTE ASH (LBWA) PARTICLE REINFORCED ALUMINIUM ALLOY (A356 ALLOY) COMPOSITES - Usman, Y.; Dauda, E. T.; Abdulwahab, M.; Dodo, R. M. (FUDMA JOURNAL OF SCIENCES, 2020)
The wear and mechanical properties of aluminium alloy (Al-Si-Mg)/ locust bean waste ash particles composites developed by stir casting were studied. The composites were based on the A356 alloy reinforced with locust bean waste ash (LBWA) particles. X-ray fluorescence (XRF) analysis on the LBWA particles was carried out. The mechanical properties tested are hardness, tensile strength and impact energy while the wear behaviour of the developed composites was studied by conducting dry sliding wear test using a ball-on-disc tribometer. Results revealed that there is a high influence of reinforcement addition on the tested mechanical properties. The wear rate decreased significantly with increasing weight fraction of LBWA particles. The highest hardness, tensile strength and wear resistance are obtained with the addition of 10% wt. LBWA particles.